Preconception care practice among pregnant women attending antenatal care at Wachemo University, Nigist Eleni Mohammed Memorial Comprehensive Specialized Hospital, southern Ethiopia, 2022: a mixed-methods study - Getu, Tadesse; Eliso, Melesech; Lodebo, Mengistu; Beraku, Tesema; Getaneh, Temesgen; Anlay, Engdaw Asmare; Yohannes, Samuel; Petrucka, Pammla; Tega, Ayenew (Frontiers in Global Women's Health, 2025)
BackgroundPreconception care includes biomedical, behavioral, and social health interventions for women and couples before conception, aiming to improve their overall health status. Despite its importance, studies conducted in Ethiopia reveal that the practice remains unacceptably low; this emphasizes the need for further investigation, particularly through mixed-methods studies incorporating women's perspectives.MethodsAn institution-based, cross-sectional study with concurrent triangulation was conducted at Wachemo University, Nigist Eleni Mohammed Memorial Comprehensive Specialized Hospital between 1 April and 30 June 2022. Quantitative data were collected using a systematic random sampling method, while qualitative data were obtained through purposive sampling. A structured, interviewer-administered questionnaire was used to collect data from 332 eligible antenatal care clients. The data were entered into EpiData and analyzed using SPSS. Bivariate and multivariate analyses were performed to identify factors associated with the practice of preconception care. A 95% confidence interval (CI) and p-values <0.05 were considered statistically significant. Thematic analysis of qualitative data was performed using ATLAS.ti version 7.ResultsThis study showed that 104 women (31.3%) (95% CI: 26.5–36.5) engaged in good preconception care practices. Factors significantly associated with good practices included attending college or university [adjusted odds ratio (AOR) = 3.52, 95% CI: 1.14–10.87], having a history of adverse pregnancy outcomes (AOR = 4.82, 95% CI: 2.20–10.58), receiving support from one’s husband (AOR = 2.45, 95% CI: 1.05–5.73), and having good knowledge of preconception care (AOR = 4.52, 95% CI: 2.11–9.68). The qualitative analysis revealed that client-related and health facility-related factors influenced the practice of preconception care.ConclusionNearly 7 out of 10 women in this study became pregnant without the utilization of any component of preconception care. To improve the practice of preconception care, it is essential to raise awareness about its benefits among all women of reproductive age. Future efforts focusing on knowledge dissemination and awareness creation to improve partner support are crucial to enhancing preconception care practices.